Potential Role of Natriuretic Response to Furosemide Stress Test During Acute Heart Failure. (16th June 2021) - Caravaca Pérez, Pedro; Nuche, Jorge; Morán Fernández, Laura; Lora, David; Blázquez-Bermejo, Zorba; López-Azor, Juan Carlos; de Juan Bagudá, Javier; García-Cosío Carmena, María Dolores; Escribano Subías, Pilar; Salguero-Bodes, Rafael; Arribas Ynsaurriaga, Fernando; Delgado, Juan F.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Poor natriuresis has been associated with a poorer response to diuretic treatment and worse prognosis in acute heart failure. Recommendations on how and when to measure urinary sodium (UNa) are lacking. We aim to evaluate UNa quantification after a furosemide stress test (FST) capacity to predict appropriate decongestion during acute heart failure hospitalization. Methods: Patients underwent an FST on day-1 of admission, and UNa was measured 2 hours after, dividing patients into low or high UNa based on the sample median value. A semiquantitative composite congestive score (CCS; 0–9) and NT pro-BNP (N-terminal pro-B-type natriuretic peptide) quantification were assessed before the FST and at day 5 after the FST. Results: Median UNa after FST in the 65 patients included was 113 (97–122) mmol/L. At day 5, a lower proportion of patients with a low UNa reached a 30% decrease in NT-proBNP levels (21 [66%] for low UNa versus 31 [94%] for high UNa; P =0.005) and an appropriate grade of decongestion (CCS<3) (20 [62%] for low UNa versus 32 [97%] for high UNa; P <0.001). A UNa>83 mmol/L 2 hours after FST had a 96% sensitivity to predict an NT-proBNP reduction ≥30% and 95% to predict a CCS<3 at day 5. Low UNa patients presented a lower cumulative diuresis and weight loss and presented more often with prolonged hospitalization, worsening heart failure, and readmission because of acute heart failure or death at 6 months. Conclusions: Low natriuresis after an FST identified patients at a higher risk of an inadequate diuretic response and an inappropriate decongestion. FST-guided diuretic treatment might help to improve decongestion, shorten hospitalizations, and to reduce adverse outcomes.